Heraldische Funeralpanegyrik des ukrainischen Barock - Erdmann, Martin (Peter Lang International Academic Publishing Group, 1999)
The presentation is based on the structure of the work in order to work out the receptive-aesthetic intention as clearly as possible. Overall, the author endeavored to present more general features of the heraldic panegyric literature in the concrete text example.
Keywords: Barock; Beispiel; Cnot; Erdmann; Funeralpanegyrik; Heraldische; Kossova; Linguistik; Literatur; Philologie; Slavische Sprachwissenschaft; Slavische Studien; Stolp; ukrainischen; vestra; Literature & literary studies